THE KHOJA ZAINUDDIN MOSQUE IN BUKHARA - BADR, JASMIN (Muqarnas, 2012)
This article presents a study of the architecture of a sumptuous and hitherto largely unknown monument in Bukhara: the Khoja Zainuddin Mosque. Situated to the southwest of the Friday mosque, the building is generally dated to the sixteenth century. It is a striking example of traditional building crafts in Central Asia after the Timurid era, a period largely neglected in works on the history of architecture in the eastern part of the Islamic world. Historical inscriptions and endowment deeds of the mosque are not known, and the information obtained from historical manuscripts is not sufficient to reconstruct its building history. However, an archaeological building survey, based on an investigation of the extraordinary and well-preserved wooden portico, mosaic panels, and wall paintings in the kundal technique, allowed for a detailed analysis of the phases of construction of the mosque, as well as of the building techniques and materials used.